Much ado about religion : a critical edition and annotated translation of the Agamadambara, a satirical play by the ninthcentury Kashmirian philosopher Bhatta Jayanta - Dezso, C (2004)
This thesis contains a critical edition and annotated translation of the Āgamaḍambara, a four act play by Bhaṭṭa Jayanta. The Āgamaḍambara is a unique college-drama written by an eminent ninth century Kashmirian naiyāyika philosopher, which gives a comprehensive picture of the contemporary religious debates as well as the 'Religionspolitik' of the royal court. The introduction provides an account of Bhaṭṭa Jayanta's life and works, placed in the intellectual and historical context of his time. The question of conservative versus pragmatic attitude towards the heterodox religious schools is also dealt with. The introduction next examines what makes Jayanta's play so unique and unorthodox. It also considers the phenomenon of 'philosophical plays' in the light of the discussions on the nature and relation of poetry and śāstra, doctrinal or scientific literature. An analysis of the dominant aesthetic mood (rasa) of the play closes this section. There follows a description of the sources consulted for the text of the Āgamaḍambara. These comprise two manuscripts in Jaina Devanāgarī script, and the editio princeps. The methodology of the edition of the Prakrit passages in classical Indian dramas in general and in the Āgamaḍambara in particular is also discussed. Three registers of apparatus contain variants to the accepted text of the play, a Sanskrit translation (chāyā) of the Prakrit sentences, and testimonia from Jayanta's magnum opus, the Nyāyamanjarī. In the notes to the translation the reader will find long quotations from various Sanskrit works. The aim of these quotations is to place Jayanta's ideas in the intellectual context of his age and thereby to make their interpretation more accurate.